Societal Poverty : A Relative and Relevant Measure - Jolliffe, Dean (World Bank, Washington, DC, 2017)
Poverty lines are typically higher in richer countries, and lower in poorer ones, reflecting the relative nature of national assessments of who is considered poor. In many high-income countries, poverty lines are explicitly relative, set as a share of mean or median income. Despite systematic variation in how countries define poverty, global poverty counts are based on fixed-value lines. To reflect national assessments of poverty in a global headcount of poverty, this paper proposes a societal poverty line. The proposed societal poverty line is derived from 699 harmonized national poverty lines, and has an intercept of $1 per day and a relative gradient of 50 percent of median national income or consumption. The societal poverty line is more closely aligned with national definitions of poverty than other proposed relative lines. By this relative measure, societal poverty has fallen steadily since 1990, but at a much slower pace than absolute extreme poverty.